Factors Influencing the Decision of Parents to LP in Pediatric with CNS Infection - Dessy Dian Antarini; Dimyati, Yazid; Rosdiana, Nelly; Fujiati, Isti Ilmiati; Destariani, Cynthea Prima (Talenta Publisher, 2019)
Lumbal Puncture (LP) is a procedure that can help to diagnosed CNS infection in children. The procedure of LP is a common invasive procedure, but sometimes it had refused by the parents. Furthermore, it can cause a delayed in the diagnosis and affected the prognosis. The subject was the parents of pediatric patients with CNS infection. We have a questionnaire and using Chi-square and Fisher exact test to analyze factors that influenced the parent’s decision of LP procedure. From the parents of 50 children with CNS infection, 19 parents (38%) were refused the LP procedure. Father’s education was related to the refusal of LP procedure with PR 6.64 (95%CI; 8.95-788.08). Mother’s education was related to the refusal of LP procedure with PR 7.69 (95%CI; 3.19-16.24). There was the significant result of the parent's education with the decision of LP procedure.